Effects of grey mangrove leaf extract (Avicennia marina) on the growth of Staphylococcus aureus - Priambodo, Bima; Budiarti, Retno; Rahadianto, Rahadianto; Nefertiti, Eva (JURNAL BIOSAINS, 2024)
The emergence and spread of methicillin-resistant Staphylococcus aureus in recent decades complicates the antibiotic therapy. The grey mangrove (Avicennia marina) has flavonoid, terpenoid, saponin, phenolic, tannin, and alkaloid chemical compounds that have antimicrobial activity, thus potentially inhibiting Staphylococcus aureus. This study aims to examine the effects of the grey mangrove (Avicennia marina) leaf extracts on the growth of Staphylococcus aureus. This research uses laboratory experimental design with disc diffusion method to test the inhibition of Staphylococcus aureus bacteria growth in Mueller-Hinton medium. There were 6 treatment groups, namely negative control of 0.2% DMSO,  positive control of amoxicillin 30 µg, Avicennia marina leaf extract at concentration of 25%, 50%, 75%, and 100%. The results of this research showed that Avicennia marina leaf extract produces inhibition zone of 7.06 mm, 8.51 mm, 10.07 mm, 13.29 mm at concentration of 25%, 50%, 75%, and 100%. Meanwhile, positive control produces inhibiton zone of 23.65 mm, and negative control has no inhibition zone. The statistical tests using one-way ANOVA resulted in a significance value of less than 0.05 (p<Î±). The conclusion of this study showed that the grey mangrove (Avicennia marina) leaf extract at 100% concentration is the most effective treatment group in inhibiting the growth of Staphylococcus aureus, although the inhibition was not much better when compared to the inhibition of the positive control group.